Challenges facing Juvenile Delinquents Rehabilitation Centres in Kenya: A Case Study of Othaya Rehabilitation Centre, Nyeri, Kenya - Kariuki , Rosalind W.; Njoka , Johannes N.; Ndegwa , Lucy W. (African Journal of Education,Science and Technology (AJEST), 2019)
Incidences of juvenile delinquency have been escalating at an alarming rate. The government has established rehabilitation centres for admitting adolescents who for some reason have had contraventions to the legal system. Rehabilitation of these children is a key component in ensuring that they are successfully empowered to live amicably in the social order. This study sought to assess the challenges facing Othaya Rehabilitation Centre, Nyeri County, Kenya. The research objective was, to assess the challenges encountered by tutors and learners in Othaya Rehabilitation Centre in Nyeri, Kenya. The research design was essentially descriptive with qualitative and quantitative approaches and was guided by B.F. Skinner’s Theory of Operant Conditioning. The target population of the study consisted of all learners and teachers in Othaya Rehabilitation Centre. There were 103 learners and 9 teachers. The study employed census survey and thus the entire population was included in the sample because it was a manageable number. The research instruments included two sets of questionnaires, one for teachers and the other for the learners. A pilot study was conducted in a neighbouring rehabilitation centre in Kirinyaga County and the data collected used to compute the reliability of the instruments using Chronbach alpha which yielded a coefficient of .810, which indicated that the instruments were reliable. Data was analyzed using descriptive statistics such as means, frequencies and percentages and the findings were presented in form of tables and narrations. The findings of the study revealed that teachers had not received any in-service training on handling juvenile delinquents, were not motivated, there were no incentives for good performance and the teachers received no parental support in molding the learners. The research established that the counseling programmes existing in the rehabilitation centre were perceived as generally effective, pupils were exposed to sporadic bullying by their colleagues, teachers were occasionally absent and missed classes and pupils had inadequate breaks to play a part in co-curricular activities. Lastly, the study revealed that there existed poor hygiene conditions and there was frequent theft of personal items. The study recommends the need to sensitize parents to provide for the physical and the psychological needs of the learners, provision of training opportunities for teachers and improvement of safety and living conditions for the learners.